The Marx Machine : Politics, Polemics, Ideology. - Barbour, Charles (Lexington Books, 2012)
This book employs recently developed techniques of literary criticism, philosophical argumentation, and bibliographical or manuscript analysis to bring Marx's early works, and especially his early polemics, into conversation with his most contemporary, post-Marxist critics. It argues that some of Marx's best known concepts - ideology and historical materialism, for example - in fact represent responses to the kinds of arguments that many people mount against them today.